Apical sealing of two retrograde filling materials in single-rooted teeth - Salcedo-Moncada, Doris Elizabeth (2020)
Aim: To compare the sealing capacity of mineral trioxide (MTA®) and tricalcium silicate (Biodentine®) for retrograde filling in single-root permanent teeth. Materials and methods: Thirty-eight permanent single-root teeth with complete apical closure were selected and randomly divided into two experimental groups (n = 15): Group 1: MTA®, and Group 2: Biodentine®, in addition to positive and negative controls. Root treatment was performed with the MTWO rotary system, and obturation was carried out by means of the continuous wave thermoplastic system (Beefill) using Grossman-type cement as a sealant. Apical end apicoectomy was performed followed by the preparation of standardized retro-apical cavities and the respective fillings with MTA ® and Biodentine® according to the study group. Subsequently, the specimens were subjected to an apical filtration process of Chinese ink and transparency, while the apical filtration was evaluated with a stereoscopic microscope. The data were analyzed with the Mann-Whitney U test. Results: Inferential analysis showed that Biodentine® had less microleakage than MTA® with a statistically significant difference of 95% (p <0.034). Conclusion: Biodentine® cement showed greater apical sealing capacity than MTA® cement in retrograde fillings of single-root teeth ex vivo.